已知:a^4+b^4+c^4+d^4= 4abcd,试证明a=b=c=d.

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/12 23:10:03

已知:a^4+b^4+c^4+d^4= 4abcd,试证明a=b=c=d.
已知:a^4+b^4+c^4+d^4= 4abcd,试证明a=b=c=d.

已知:a^4+b^4+c^4+d^4= 4abcd,试证明a=b=c=d.
题目不对
不如
a=1,b1,c=-1,d=-1
这个式子成立,但结论不对

由a^4+b^4-2a²b²+2a²b²+c^4+d^4-2c²d²+2c²d²-4abcd0
(a²-b²)²+(c²-d²)²-2(a²b²-4abcd+c²d²)=0
(a+b)²(a-b...

全部展开

由a^4+b^4-2a²b²+2a²b²+c^4+d^4-2c²d²+2c²d²-4abcd0
(a²-b²)²+(c²-d²)²-2(a²b²-4abcd+c²d²)=0
(a+b)²(a-b)²+(c+d)²(c-d)²+2(ab-cd)²=0
当a>0,b>0,c>0,d>0时,a=b=c=d成立。
由柯西不等式a^4+b^4+c^4+d^4》4abcd 当a=b=c=d 时 等号成立
所以a=b=c=d 四边形为棱形

收起

由a^4+b^4-2a²b²+2a²b²+c^4+d^4-2c²d²+2c²d²=4abcd
(a*2-b^2)^2+(c^2-d^2)^2+2(a^2b^2-4abcd+c^2d^2)=0
(a+b)^2(a-b)^2+(c+d)^2(c-d)^+2(ab-cd)^2=0
所以a=b,c=d,ab=cd
所以a=b=c=d